2009
DOI: 10.1007/s11670-009-0310-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiofrequency ablation on lymphocyte subsets and type 1/type 2 T cell subpopulations in patients with hepatocellular carcinoma

Abstract: Objective: To evaluate whether radiofrequency ablation (RFA) might have an influence on immune status in hepatocellular carcinoma (HCC) patients.Methods: We measured the T lymphocytes, B lymphocyte and NK cells, and determined the population of Th1, Th2, Tc1 and Tc2 of peripheral blood samples taken from 26 HCC patients before and after RFA.Results: The proportion of Type1 cells (Th1 and Tc1) and NK cells were significantly increased after RFA, especially in patients of the following subgroups: male, age>55 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Deep sequencing of T cell receptors from patients in this cohort showed that whereas high magnitude clonal expansion (.1000 copies) did occur with cryoablation alone, the number of clones that exhibited high magnitude clonal expansion doubled with the addition of ipilimumab (20). RFA of HCC also produces increases in CD4 cells, with a 19% increase in Th1 populations, which aid in CD8 cell costimulation (99). RFA of HCC also leads to a nearly 60% increase in natural killer (NK) cell populations in humans, and the functionality of these NK cells (as indicated by inferon (INF) γ production) strongly predicts survival after RFA (100).…”
Section: Combining Io Therapies With Immunotherapymentioning
confidence: 84%
“…Deep sequencing of T cell receptors from patients in this cohort showed that whereas high magnitude clonal expansion (.1000 copies) did occur with cryoablation alone, the number of clones that exhibited high magnitude clonal expansion doubled with the addition of ipilimumab (20). RFA of HCC also produces increases in CD4 cells, with a 19% increase in Th1 populations, which aid in CD8 cell costimulation (99). RFA of HCC also leads to a nearly 60% increase in natural killer (NK) cell populations in humans, and the functionality of these NK cells (as indicated by inferon (INF) γ production) strongly predicts survival after RFA (100).…”
Section: Combining Io Therapies With Immunotherapymentioning
confidence: 84%
“…[ 23 ] When ACHr-AB is combined with acetylcholine receptor (AChR), the complement cascade is activated, resulting in abnormal normal physiological structure of the postsynaptic membrane and changes in the degradation rate and structure of AChR, thus reducing the number of AChR with normal physiological function, blocking signal transmission between muscles, and leading to the occurrence of diseases. [ 24 ] Many scholars have reported [ 25 , 26 ] that the disorder of T lymphocyte subsets is one of the important factors of the abnormal immune regulatory system. Among them, the CD3 + subgroup in T lymphocytes is involved in the recognition of antigens and signaling of T lymphocytes; the CD4 + subgroup content in T lymphocytes can induce and assist humoral immunity, while CD8 + suppresses humoral immunity.…”
Section: Discussionmentioning
confidence: 99%